The materiality of things? Bruno Latour, Charles Péguy and the history of science. (February 2013) - Schmidgen, Henning
This article sheds new light on Bruno Latour's sociology of science and technology by looking at his early study of the French writer, philosopher and editor Charles Péguy (1873–1914). In the early 1970s, Latour engaged in a comparative study of Péguy's Clio and the four gospels of the New Testament. His 1973 contribution to a Péguy colloquium (published in 1977) offers rich insights into his interest in questions of time, history, tradition and translation. Inspired by Gilles Deleuze's philosophy of difference, Latour reads Clio as spelling out and illustrating the following argument: 'Repetition is a machine to produce differences with identity'. However, in contrast to Deleuze's work (together with Félix Guattari) on the materiality of machines, or assemblages [ agencements ], Latour emphasizes the semiotic aspects of the repetition/difference process. As in Péguy, the main model for this process is the Roman Catholic tradition of religious events. The article argues that it is this reading of Péguy and Latour's early interest in biblical exegesis that inspired much of Latour's later work. In Laboratory Life (Latour and Woolgar, 1979) and The Pasteurization of France (1988) in particular, problems of exegesis and tradition provide important stimuli for the analysis of scientific texts. In this context, Latour gradually transforms the question of tradition into the problem of reference. In a first step, he shifts the event that is transmitted and translated from the temporal dimension (i.e. the past) to the spatial (i.e. from one part of the laboratory to another). It is only in a second step that Latour resituates scientific events in time. As facts they are 'constructed' but nevertheless 'irreducible'. They result, according to Latour, from the tradition of the future. As a consequence, the Latourian approach to science distances itself from the materialism of Deleuze and other innovative theoreticians.